Design Controller for a Class of Nonlinear Pendulum Dynamical System - Mohamad Reza Rahimi Khoygani; Reza Ghasemi; Davoud Sanaei (IAES International Journal of Artificial Intelligence (IJ-AI), 2013)
Designing proportional integral derivative (PID), Linear Quadratic Regulator (LQR), Fuzzy Logic Controller (FLC) and Self-Tuning Fuzzy PID (STFP) controller is used for nonlinear pendulum dynamic system in this paper.The promising performance of the proposed controllers investigates in simulation. The effectiveness, robustness against noise and the comparison of the controller methods for Nonlinear Pendulum Dynamical System are delivered in this paper.DOI: http://dx.doi.org/10.11591/ij-ai.v2i4.4164